Incidence of Strict Quality Standards: Protection of Consumers or Windfall for Professionals? - Daiji Kawaguchi; Tetsushi Murao; Ryo Kambayashi (Institute for the Study of Labor (IZA), 2013)
This paper examines the effects of upgrading product quality standards on product and professional labor-market equilibriums when both markets are regulated. The Japanese government revised the Building Standards Act in June 2007, requiring a stricter review process for admitting the plans of large-scale buildings. This regulatory change increased the wage of certified architects in Tokyo by 30% but did not increase their total hours worked because of an inelastic labor supply. The stricter quality standards created a quasi-rent for certified architects and owners of condominiums at a cost to consumers. Evidence suggests that the stricter quality standards increased the transaction price of used condominiums by 15% in the Tokyo metropolitan area.
Keywords: J44; 330; labor market of professionals; product standard; safety regulation; incidence of government regulation